Prevalence of depression in patients with sarcopenia and correlation between the two diseases: systematic review and meta‐analysis. Issue 1 (8th January 2022) - Li, Zhenzhen; Tong, Xiang; Ma, Yao; Bao, Ting; Yue, Jirong
Abstract: Background: Depression may be the most common cause of emotional distress later in life and can significantly reduce the quality of life in elderly individuals. Sarcopenia is a syndrome characterized by the continuous loss of skeletal muscle mass and decreased strength and function. In recent years, many studies have shown a correlation between sarcopenia and depression. The present study aimed to investigate the prevalence of depression among individuals with sarcopenia and to ascertain whether sarcopenia is independently associated with depression. Methods: We systematically searched the PubMed, Embase, and Google Scholar databases for papers on sarcopenia published up to 31 August 2021. We reviewed the literature on the number of individuals with sarcopenia, the number of individuals with both sarcopenia and depression, and the odds ratio (OR) of sarcopenia to depression. Statistical analyses were performed using Meta‐DiSc 1.4 software and Stata version 12.0. Results: Nineteen articles met the inclusion criteria for review: nine reported both prevalence and ORs, four described prevalence only, and six detailed the ORs only. Regarding prevalence, there were 1476 cases of sarcopenia and 364 of depression in the selected studies; the mean age of the patients was 75.5 years, and the overall prevalence of depression was 0.28 [95% confidence interval (CI): 0.21–0.36]. Significant heterogeneity was noted ( P < 0.001; I 2 = 92.2%). In the case of ORs, there were 16 869 subjects with a mean age of 73 years; the overall adjusted OR between sarcopenia and depression was 1.57 (95% CI: 1.32–1.86). Significant heterogeneity was noted in the adjusted ORs ( P < 0.001; I 2 = 75.1%). Conclusions: The prevalence of depression in patients with sarcopenia was high relatively, and there was a correlation between sarcopenia and depression.